Luovuuden merkitys palloilulajien pelitilanteissa : pelitilanneluovuus osana valmennusfilosofiaa - Lehto, Antti (2024)
Aim of the study was to investigate coaches understanding of creativity in team ball sports (TBS) context. The coaches were asked how they see creativity in TBS, how it should be taken into account in daily coaching activities and whether it can be used to achieve a competitive advantage. Creativity is important in TBS, as it improves the chances of creating a competitive advantage in game situations. It is more challenging to play against a game style, or player, which is difficult to predict.